Highly concentrated collagen/chondroitin sulfate scaffold with platelet-rich plasma promotes bone-exposed wound healing in porcine - Li, Zhihao; Li, Qian; Ahmad, Akhlaq; Yue, Zhongjie; Wang, Hongxia; Wu, Guofeng (Frontiers in Bioengineering and Biotechnology, 2024)
In the case of wounds with exposed bone, it is essential to provide not only scaffolds with sufficient mechanical strength for protection, but also environments that are conducive to the regeneration of tissues and blood vessels. Despite the excellent biocompatibility and biodegradability of collagen and chondroitin sulfate, they display poor mechanical strength and rapid degradation rates. In contrast to previous methodologies that augmented the mechanical properties of biomaterials through the incorporation of additional substances, this investigation exclusively enhanced the mechanical strength of collagen/chondroitin sulfate scaffolds by modulating collagen concentrations. Furthermore, platelet-rich plasma (PRP) was employed to establish optimal conditions for vascular and tissue regeneration at the wound site. Highconcentration collagen/chondroitin sulfate (H C-S) scaffolds were synthesized using high-speed centrifugation and combined with PRP, and their effects on endothelial cell proliferation were assessed. A porcine model of bone-exposed wounds was developed to investigate the healing effects and mechanisms. The experimental results indicated that scaffolds with increased collagen concentration significantly enhanced both tensile and compressive moduli. The combination of H C-S scaffolds with PRP markedly promoted endothelial cell proliferation. In vivo experiments demonstrated that this combination significantly accelerated the healing of porcine bone-exposed wounds and promoted vascular regeneration. This represents a promising strategy for promoting tissue regeneration that is worthy of further exploration and clinical application.